Policy analysis matrix as an appropriate tool in assessing the extent of governmental interventions in agriculture - Jernej TURK (Acta Agriculturae Slovenica)
The concept of Policy Analysis Matrix (PAM) is used to demonstrate the extent of governmental interventions in economy and to unravel the sources of comparative advantages and divergences within it. PAM measures a degree to which observable market prices for a particular farm product differ from efficiency (social) prices. This analysis clearly shows the impact of governmental interventions in agricultural production, where private and social profitabilities are evaluated on the basis of existing private and social revenues and costs that occur inside the given farm system. The importance of applying PAM tools for the purpose of investigating numerous policy effects is especially apparent in agricultural systems undergoing transition. Various PAM coefficients derived in this study reveal a contrasting attitude of a government in treating the market of two (hypothetically taken) farm products. This has resulted in the existence of a comparative advantage for one agricultural good and in the social non-profitability for another farm commodity.